2014
DOI: 10.3389/fpsyt.2014.00009
|View full text |Cite
|
Sign up to set email alerts
|

Latent Classes of Substance Use in Adolescent Cannabis Users: Predictors and Subsequent Substance-Related Harm

Abstract: Cannabis use is highly prevalent in late adolescence, but not all users experience significant negative consequences. Little information is available to identify the substance use patterns and risk factors of users who are at greater risk of experiencing negative consequences. In this prospective study, we aimed to empirically identify latent classes of substance use in adolescent cannabis users and to examine how these classes relate to antecedent psychosocial predictors and subsequent substance-related outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
(75 reference statements)
2
20
0
Order By: Relevance
“…Poly drug use has been linked with a variety of medical, psychological, and psychosocial harms among adolescents (Bohnert et al, 2014;Fallu et al, 2014;Felton et al, 2015;Kelly, Chan, et al, 2015;Kelly, Evans-Whipp, et al, 2015;Peters et al, 2012). The severity of these harms highlights the importance of identifying the factors that contribute to the consumption of multiple substances to inform future prevention programs (Hublet et al, 2015;Marshall, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly drug use has been linked with a variety of medical, psychological, and psychosocial harms among adolescents (Bohnert et al, 2014;Fallu et al, 2014;Felton et al, 2015;Kelly, Chan, et al, 2015;Kelly, Evans-Whipp, et al, 2015;Peters et al, 2012). The severity of these harms highlights the importance of identifying the factors that contribute to the consumption of multiple substances to inform future prevention programs (Hublet et al, 2015;Marshall, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This was deemed a "small but notable proportion" by the authors (p.632). Poly drug use by adolescents has been linked with school non-completion, low academic achievement, psychosocial problems, depressive symptoms, psychological distress, legal problems, interpersonal difficulties, risky sexual practices, and physical health issues (Bohnert et al, 2014;Connell, Gilreath, & Hansen, 2009;Fallu, Brière, & Janosz, 2014;Felton, Kofler, Lopez, Saunders, & Kilpatrick, 2015;Kelly, Chan, Mason, & Williams, 2015;Kelly, Evans-Whipp, et al, 2015;Peters et al, 2012). Poly drug use among adolescents thus represents a significant public health issue, resulting in calls for a more comprehensive and integrated approach to youth prevention programs (Camenga, Klein, & Roy, 2006;Hale, Fitzgerald-Yau, & Viner, 2014;Leatherdale, Hammond, & Ahmed, 2008;Wiefferink et al, 2006).…”
Section: Factors Associated With Poly Drug Use In Adolescentsmentioning
confidence: 99%
“…Polydrug use in adolescence is common; for example, 41% of U.S. 10th graders (μ age = 16) reported concurrent use of tobacco, alcohol, and marijuana in 2010 (Conway, Vullo, Nichter, et al, 2013). Polydrug use is associated with worse health and social outcomes (Fallu, Brière, & Janosz, 2014; Kelly, Evans-Whipp, Smith, et al, 2015) compared to single-substance use, including cognitive deficits (Hanson, Medina, Padula, et al, 2011) and substance-related legal, relational, and work problems in young adulthood (Griffin, Bang, & Botvin, 2010). Moreover, adolescent smokers and polydrug users are more likely to report symptoms of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a single substance (e.g., alcohol, marijuana, or other drugs) anytime during childhood, adolescence, and emerging adulthood predicts major depressive disorder at age 27, (Brook et al, 2002) and both current and lifetime nicotine dependence are associated with persistent depressive symptoms (Hu, Davies, & Kandel, 2006). Each of these outcomes is linked to enduring physical, social, and mental health problems, the consequences of which are more severe for adolescents who initiate early (Fallu et al, 2014; Taylor, Malone, Ianoco, et al, 2002). Hence, it is important to identify dominant patterns of polydrug use among adolescent smokers to best inform prevention and cessation interventions in this high-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…First, Serafini et al ( 8 ) explore the possible role of hopelessness as a mediator in the relationship between early cannabis use and suicidal behaviors, while Little et al ( 9 ) investigate predictors of cannabis cessation within a sample of high-school students. The next article, by Fallu et al ( 10 ), reports the findings of a latent class analysis of adolescent cannabis users, revealing four different use trajectories. The early onset, heavy cannabis and polydrug use group in this study were found to experience the highest level of use-related problems, followed by the late-heavy-polydrug group.…”
mentioning
confidence: 97%